The Roles of the United Nations Human Right Council (UNHRC) in Handling the Human Rights Cases in political Prison Camp North Korea - Ananda Khaerunnisa (Mediasi: Journal of International Relations, 2022)
This research examines how the United Nations Human RightsCouncil (UNHRC) plays a role as an international organization, namely inhandling casesof human rights violations that afterward in the political prisoncamp in North Korea. North Korea's human rights violations occurred inseveral aspects, one of which was by settings up a camp US a low-level officewhich start when North Koreawas facing the peak of famine in 2002. thegovernment respondents to thisphenomenon by establishing manywork campsand calling for hard work in returnsfor this phenomenon. This study aims tofind out how the steps were taken UNHRC in handling human rights casesthatafterward at the political Prison Campin North Korea from the perspective ofInternational Relations studies in terms of the concept of InternationalOrganization and Human security. this study appliesa qualitative researchmethod approach with descriptive analysis sourced from secondary datathrough observation with documents based on the concepts used in thisresearch. The results of this study indicate that UNHRC is moving in itsdirection role, namely the state which acts as a body that empowers the roleof OI by forming a Commission of Inquiry (COI), Universal Periodic Review(UPR), and Special Reporter to investigate systematic human rights violationsagainst North Korea. The detainees and their families are in line with thedefinition of an individual in Islam, namely those who maintain the inner orNon-material Dimensions to protectthe basic needs of al-dharuriyyatalkhamsah . that way NorthKorea has really set aside some of its country'spriorities and the welfare of its people.Keywords: UNHRC, political Prison camp, Commission of Inquiry(COIs),Universal periodic Reviews (UPR), Special Reporter.